Perencanaan Strategis SI/TI Menggunakan Metode Ward and Peppard (Studi Kasus : Bale Hidroponik Salatiga) - Fla Prameswari; Agustinus Fritz Wijaya (APTIKOM SUMSEL, 2022)
In the current era of information development, companies are required to be able to innovate and compete with other companies. The sales process at the Salatiga Hydroponic Bale currently utilizes simple but not optimal information technology. Thus, IS/IT Strategic Planning was made to analyze internal and external business and determine IS/IT strategies for selling organic and hydroponic vegetables at Bale Hydroponics Salatiga to make it more profitable in the future. Data collection in this study used descriptive research methods with a qualitative approach. The method used in this research is the Ward and Peppard method with analysis tools namely Value Chain, SWOT (Strengths, Weaknesses, Opportunities, and Threats), McFarlan Strategic Grid. This research produces an IS/IT proposal which is mapped using the McFarlan Strategic Grid and produces an output in the form of recommendations for the company from the analysis of the IS/IT internal and external business environment within the company.